The Controversy on Transfer of Absolute Competency of the State Administrative Courts in Government Administrative Law - Yodi Martono Wahyunadi; Bart Jansen; Alwan Hadiyanto (Unissula, 2025)
The absolute competence of the State Administrative Court is to adjudicate objects of state administrative disputes in the form of State Administrative Decisions. This study aims to analyze the transitional provisions in government administration regulations and analyze the absolute competence of state administrative courts. This study is a normative legal study. The results of this study state that the transitional provisions in the Government Administration regulations in particular have changed the meaning of State Administrative Decisions in a veiled manner, which is contrary to the principle of forming laws and regulations. The absolute competence of the State Administrative Court has been expanded to include testing for abuse of authority, state administrative actions, and the concept of positive fictitious decisions, namely considering a request to be granted if the authorized official does not issue a decision within a certain time limit. In order to fulfill the principle of legal certainty and regulatory hierarchy, changes to State Administrative Decisions should be made through changes to the State Administrative Court Law, not through transitional provisions in the State Administrative Law.